2020
DOI: 10.1007/s13595-020-01010-7
|View full text |Cite
|
Sign up to set email alerts
|

Defining correct dormancy class matters: morphological and morphophysiological dormancy in Arecaceae

Abstract: & Key message Dormancy in Arecaceae diaspores is due to underdeveloped embryos, therefore, morphological dormancy or morphophysiological dormancy. Consequently, claims such as external seed structures inhibit germination, embryos are fully developed at maturity, and underdeveloped embryo is not a form of dormancy are rejected, because embryo size of the diaspore at the time of dispersal was not taken into consideration. The re-classification proposal for moving morphological dormancy into non-dormancy is also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…MD refers to the dormancy due to the small embryo size, incomplete development, or lack of differentiation after seed maturation. The morphology of the seed embryo is generally spatulate, rudimentary, or linear; in some species, it occupies ≤1% of the seed volume (Jaganathan, 2020;Liu et al, 2020). For example, the Lamprocapnos spectabilis seed endosperm comprises the entire internal tissue of the seed, and the embryo is almost invisible (Cho et al, 2020).…”
Section: Dormancy Class and Potential Factorsmentioning
confidence: 99%
“…MD refers to the dormancy due to the small embryo size, incomplete development, or lack of differentiation after seed maturation. The morphology of the seed embryo is generally spatulate, rudimentary, or linear; in some species, it occupies ≤1% of the seed volume (Jaganathan, 2020;Liu et al, 2020). For example, the Lamprocapnos spectabilis seed endosperm comprises the entire internal tissue of the seed, and the embryo is almost invisible (Cho et al, 2020).…”
Section: Dormancy Class and Potential Factorsmentioning
confidence: 99%
“…1 D) may also delay root formation and development. Our previous work (yet to be published) revealed that D. involucrata seeds have physical dormancy + deep physiological dormancy based on a recent description by Jaganathan (2020) .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…They have both a morphological, that is, embryo not fully grown (underdeveloped) at seed maturity, and a physiological, that is, require a period of afterripening or warm stratification to germinate, component of dormancy. Thus, the diaspores have some kind of MPD (Perez et al, 2008;Baskin and Baskin, 2014b;Rajapakshe et al, 2017;Jaganathan, 2020Jaganathan, , 2021Jaganathan et al, 2021). For palms with the remote tubular and remote ligular types of seedling formation (see Baskin and Baskin, 2014b) For B (rs) ′ b ′ , B indicates an underdeveloped embryo (i.e.…”
Section: Seed Dormancy Classification With Particular Reference To the Monocots Palms And Cannamentioning
confidence: 99%